ANALISIS PENENTUAN KARYAWAN TERBAIK MENGGUNAKAN METODE SAW PADA PT NEXUS ENGINEERING INDONESIA - FERNANDO FERNANDO (STMIK KAPUTAMA, 2023)
This study aims to make Simple Additive Weighting programming to determine the best employees at PT Nexus Engineering Indonesia. The method that will be used by the author is the Simple Additive Weighting method which allows us to find the total of each performance on various alternatives for all attributes. The criteria used for this study consist of 5, namely work results, attendance, attitudes, teamwork, and delays. The use of the Simple Additive Weighting method is expected to help decision making for determining the best employees at PT Nexus Engineering Indonesia which so far is still subjective. In this research we will solve problems related to determining the best employees. The data is obtained from human resource development which will be followed by determining the weights for the criteria and sub-criteria. The final result will be a ranking of the alternatives or names of the best employees at PT Nexus Engineering. The results obtained from this study are expected to be taken into consideration to determine the best employees more objectively.